Notes on the ecology of Phyllodactylus reissi (Phyllodactylidae: Sauria) in Parque Nacional Cerros de Amotape (Tumbes, Peru) - Jordán Arizmendi, Juan Carlos (2011)
Some basics aspects on the ecology of the nocturnal gecko Phyllodactylus reissi from Parque Nacional Cerros de Amotape (Tumbes, Peru) are described. This species used rock boulders (57,4%) and trees (31,9%) as microhabitats primarily, exhibiting a nocturnal activity pattern, with a peak between 2100-2200 hours, remaining active until midnight. Body temperature (mean 24,4 ºC) was correlated with both air and substrate temperature, with the last variable affecting in higher degree (47%) the body temperature of this species. The slightly high body temperature of Phyllodactylus reissi, compared to other Phyllodactylus geckos, could be related to nocturnal microhabitat use and diurnal retreat site selection. More studies on lizard ecology from this endangered ecosystem are needed.